About the science of pedagogy (how to avoid the transformation of pedagogical science into ideology) - I. P. Smirnov (Образование и наука)
Introduction. Numerous declarative official statements on the key role of education and scientific-pedagogical knowledge to ensure the well-being of the nation and the sustainable development of Russia in the modern world directly contradict the situation in this strategically significant social area. Thus, when merging two specialised academies (medical and agricultural sciences) with alma mater – the Russian Academy of Sciences (RAS), the Russian Academy of Education (RAE) was not included in the list of the elected representatives, which may indirectly demonstrate the “inferiority” of scientific pedagogy, calling into question its mission in the development of education.The aim of the article is to discuss the conditions and prerequisites for the possible loss of scientific status by pedagogy, its transformation into ideology and the replacement of pedagogical principles of education development by ideological ones.Methodology and research methods. In the course of the research, the methods of the system-based, retrospective and comparative analysis, synthesis and generalisation were employed.Results and scientific novelty. The author of the present publication considers and analyses the origins of scientific pedagogy and its essential definitions in the works of classical scholars – K. D. Ushinsky, L. N. Tolstoy, P. F. Kapterev, V. P. Vakhterov, K. N. Ventzel, etc. with contemporary interpretation of scientific status of pedagogical branch of knowledge. The paper highlights the impact on its reorganisation, content transformations of political and social processes, as well as transformations of governmental management structures. It has been proved that the reforms of the Russian science carried out in recent years consistently lead to the loss of scientific status by pedagogy, to the loss of academic principle “science should be managed by scientists” and to the transformation of scientific institutions into subordinate structures. Contrary to the Article 13 of the Constitution of the Russian Federation, which states that “no ideology may be established as state or mandatory”, there is a conversion of pedagogy into ideology. The classical pedagogical foundations evolutionary development inherent in scientific knowledge are deformed by current ideological attitudes, nullifying the constitutional guarantee (Article 44) on freedom of literary, artistic, scientific, technical and other forms of creativity. The depoliticisation of educational sphere and pedagogical science was planned at the end of the 20th century but it was abandoned. Therefore, the author emphasises the importance of such process.Practical significance. The assessments and conclusions presented in the article create methodological prerequisites for developing a discussion about the mission of pedagogical science in modern Russian society, adjusting scientific reforms and, as a result, freeing education from ideological violence.